2007
DOI: 10.1614/wt-06-151.1
|View full text |Cite
|
Sign up to set email alerts
|

Weed and Peanut (Arachis Hypogaea) Response to Diclosulam Applied Post

Abstract: Diclosulam is generally applied either PPI or PRE to peanut to control certain broadleaf weeds and suppress sedges. Research was conducted to determine efficacy and peanut response to POST applications of diclosulam at 9, 13, 18, and 27 g ai/ha. Efficacy of diclosulam was affected by application rate and environment. Common ragweed control ranged from 60 to 100%, entireleaf morningglory control from 56 to 100%, marestail control from 78 to 85%, and nodding spurge from 50 to 97%. Smooth pigweed and common lambs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 18 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…Diclosulam, lactofen, and 2,4-DB did not negatively affect pod yield when compared with non-treated peanut. Other research (Lancaster et al, 2007) demonstrated no detrimental effect of diclosulam applied POST to peanut 7 to 35 d after planting prior to the R1 stage of growth (Boote, 1982). Diclosulam can be applied up to 30 d after planting with minimal concern for negative impact on peanut (Anonymous, 2004;Prostko, 2004).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Diclosulam, lactofen, and 2,4-DB did not negatively affect pod yield when compared with non-treated peanut. Other research (Lancaster et al, 2007) demonstrated no detrimental effect of diclosulam applied POST to peanut 7 to 35 d after planting prior to the R1 stage of growth (Boote, 1982). Diclosulam can be applied up to 30 d after planting with minimal concern for negative impact on peanut (Anonymous, 2004;Prostko, 2004).…”
Section: Resultsmentioning
confidence: 96%
“…Imazapic, lactofen, and 2,4-DB can be applied no closer to harvest than 90, 45, and 45 d, respectively (Anonymous, 2015;Anonymous, 2016;Anonymous, 2014a). Imazapic and lactofen are marginally effective on Palmer amaranth and morningglory that are large (Chahal et al, 2011;Lancaster et al, 2005Lancaster et al, 2007 or express resistance to ALS-inhibiting herbicides which is widespread in North Carolina (Poirier et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although common ragweed was present across the entire field, the population density varied, and it is suspected that selection pressure for ALS-resistant biotypes most likely varied across the field based on previous cropping systems or herbicide program. Previous research (Everman et al 2006;Lancaster et al 2007) reported that diclosulam applied POST at the manufacturer's suggested use rate of 26 g ha 21 controlled ALS-susceptible common ragweed completely.…”
Section: Resultsmentioning
confidence: 99%
“…ragweed, the rate required to avoid significant peanut injury is considered low for many weed species (Anonymous 2010b). Additionally, common ragweed that is not resistant to ALS-inhibiting herbicides is considered very susceptible to diclosulam (Bailey et al 1999;Lancaster et al 2007). In experiments evaluating reduced herbicide programs in peanut with rates at or below the manufacturer's suggested use rate, diclosulam, either PRE or POST, consistently controlled common ragweed when applied at rates lower than 26 g ha 21 (Grey et al 2001;Lancaster et al 2007).…”
Section: Resultsmentioning
confidence: 99%